Study design and protocol of a low to high intensity computer-based cognitive training at home in supplement to standard care in patients with AD - Bernard Croisile; Samar Dimachki; Franck Tarpin-Bernard; Hanna Chainay (BMJ Open)
Introduction Recent studies on cognitive training in patients with Alzheimer’s disease (AD) showed positive long-term effects on cognition and daily living, suggesting remote computer-based programmes to increase training sessions while reducing patient’s travelling. The aim of this study is to examine short-term and long-term benefits of computer-based cognitive training at home in patients with mild to moderate AD, as a complement to the training in speech and language therapists’ (SLT) offices. The secondary purpose is to study training frequency required to obtain noticeable effects.Methods and analyses This is a national multicentre study, conducted in SLT offices. The patients follow training in one of three conditions: once a week in SLT office only (regular condition) and once a week in SLT office plus one or three times per week at home. The trainings’ content in SLT office and at home is identical. For all three groups near and far transfer will be compared with evaluate training frequency’s effect. Our primary outcome is executive and working memory scores in experimental tasks, and the secondary is neuropsychological tests and questionnaires’ scores. Linear models’ analyses are considered for all measures with a random intercept for patients and another for per practice. The fixed effects will be: three modality groups and time, repeated measures, (T0—pretraining, T1—post-training, T2—long-term follow-up) and the interaction pairs.Ethics and dissemination The study got ethics approval of the national ethical committee CPP Sud Méditerranée III (No 2019-A00458-49) and of the National Commission for Information Technology and Liberties (No 919217). Informed consent is obtained from each participant. Results will be disseminated in oral communications or posters in international conferences and published in scientific journals.Trial registration number NCT04010175.